2012
DOI: 10.3851/imp1939
|View full text |Cite
|
Sign up to set email alerts
|

Educational Gradient in HIV Diagnosis Delay, Mortality, Antiretroviral Treatment Initiation and Response in a Country with Universal Health Care

Abstract: We found important differences by educational level in diagnosis delay, virological and immunological responses to cART and mortality in a country with universal health care. Women with high educational level are at higher risk of having delayed HIV diagnoses. Educational level should be taken into account when designing HIV testing and clinical management strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
32
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 24 publications
7
32
0
1
Order By: Relevance
“…Less than 1 in 10 were initiated on ART within a week of diagnosis. The time to ART was lower than reported elsewhere globally and similar to a study from Malawi (for the year 2011) [511]. However, this has to be interpreted with caution as the eligibility criteria might vary based on the study site and period.…”
Section: Discussionsupporting
confidence: 44%
See 1 more Smart Citation
“…Less than 1 in 10 were initiated on ART within a week of diagnosis. The time to ART was lower than reported elsewhere globally and similar to a study from Malawi (for the year 2011) [511]. However, this has to be interpreted with caution as the eligibility criteria might vary based on the study site and period.…”
Section: Discussionsupporting
confidence: 44%
“…Studies globally have reported a long time to enter into care and/or initiate ART after HIV diagnosis [511]. The enrolment and ART initiation delay (Figure 1) can be due to underlying factors like client readiness/refusal, physical disability and physician concerns to defer ART initiation during the treatment of co-morbidities especially anti-TB treatment [6,8,10].…”
Section: Introductionmentioning
confidence: 99%
“…This association has also been found in other studies [6,7,14,19,21] in addition to a lower level of education (a surrogate marker of socioeconomic status) [24,25]. In a study in London, a sub-Saharan origin was associated with a two-fold higher risk of diagnosis with advanced disease than the natives after adjusting for gender and risk group [5].…”
Section: Mortalitysupporting
confidence: 61%
“…In women, liver-related SMR was 38 times higher than for women of the general population of the same age. These differences may be explained by the relative low liver-related death in women from the general population [35], together with the special characteristics of the HIV positive women; a higher prevalence of co-morbidities (29.5% of women in this study were current or former injecting drug users and 40.2% were co-infected with HCV) and their lower socio-economic level [36].…”
Section: Discussionmentioning
confidence: 96%